2019
DOI: 10.3389/fvets.2019.00019
|View full text |Cite
|
Sign up to set email alerts
|

Role of Feed Processing on Gut Health and Function in Pigs and Poultry: Conundrum of Optimal Particle Size and Hydrothermal Regimens

Abstract: The aim is to give an overview of available literature data on the role of feed processing on gut health and function with specific focus on particle size and hydrothermal processing. In addition, influence of feed processing on efficacy of exogenous feed enzymes will be discussed. The current feed processing technologies are such that ingredient choices and diet form are refined to improve feed intake and nutrient utilization efficiency. Finer feed particle size enables optimal nutrient utilization and enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
76
1
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(85 citation statements)
references
References 109 publications
0
76
1
8
Order By: Relevance
“…We also expect that use of complex diet components is beneficial for discovery of physiologically relevant phenotypes that may otherwise be lost or artificially altered on more defined diets. For example, food particle size in animal gut ecosystems is known to impact digestion and bulk passage rate as well as microbiome composition through attachment and microcolony support (Cheng et al 1981;Martz and Belyea 1986;Bjorndal et al 1990;McAllister et al 1994;Vermeulen et al 2018;Kiarie and Mills 2019). Ultimately, what is important is that researchers understand the nutritional implications of the diets they use and look to nutritional information as a resource to aid in analysis of results and comparison across laboratories.…”
Section: Does D Melanogaster Need a Standard Diet?mentioning
confidence: 99%
“…We also expect that use of complex diet components is beneficial for discovery of physiologically relevant phenotypes that may otherwise be lost or artificially altered on more defined diets. For example, food particle size in animal gut ecosystems is known to impact digestion and bulk passage rate as well as microbiome composition through attachment and microcolony support (Cheng et al 1981;Martz and Belyea 1986;Bjorndal et al 1990;McAllister et al 1994;Vermeulen et al 2018;Kiarie and Mills 2019). Ultimately, what is important is that researchers understand the nutritional implications of the diets they use and look to nutritional information as a resource to aid in analysis of results and comparison across laboratories.…”
Section: Does D Melanogaster Need a Standard Diet?mentioning
confidence: 99%
“…Early experimentations showed that supplementation of these enzymes in diets rich in viscous feedstuffs improved digestibility, growth performance and reduced feed costs (21)(22)(23). These studies helped scientists to understand the modes of action and stimulated further research and development efforts to innovate novel activities targeting specific substrates and stabilized to withstand the rigors of feed processing and gastrointestinal conditions (26). Indeed, the utility of feed enzymes in nonruminant nutrition is widely accepted (21-23, 25, 27).…”
Section: Feed Enzymesmentioning
confidence: 99%
“…However, extrusion reduced both total and viable yeast counts. Majority of poultry diets are subjected to rigorous feed processing including particle size reduction and hydrothermal processing to improve feed efficiency and hygiene (26). Suggesting that survival of unprotected yeast cells would be expected to be low in poultry feed subjected to hydrothermal processing.…”
Section: Live Whole Yeastmentioning
confidence: 99%
“…In recent years, the interest in feed particle size has increased and the feed industry continues to search for ways to optimise and improve feed utilisation, animal health including that of foot pads and growth performance [1]. Various technologies for treating of feed ingredients and compound feeds are available for the feed industry.…”
Section: Introductionmentioning
confidence: 99%